2021
DOI: 10.1108/ijshe-10-2020-0409
|View full text |Cite
|
Sign up to set email alerts
|

Campus sustainability in the Australian higher education sector: divergence and convergence in planning, reporting and tactics

Abstract: Purpose This study provides a country-specific and sector-wide study of campus sustainability. Campus sustainability is a key consideration for the higher education (HEI) sector, and campus sustainability officers and managers manage its reporting and planning. Global and country-specific studies to date have focussed on individual organisation narratives, interviews with faculty and management and content analysis of reports and plans. Findings show wide divergence on scope and scale of formalised planning an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 128 publications
0
8
0
2
Order By: Relevance
“…Furthermore, studies indicated several national instruments that should be followed to obtain better reports. In Australia, there is an Australasian Campuses Towards Sustainability, a non-profit organization that drives change toward sustainability (Melles et al , 2022). China has the Instruction on Social Responsibility Report of Shanghai’s Civilized Organizations (Yalin et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, studies indicated several national instruments that should be followed to obtain better reports. In Australia, there is an Australasian Campuses Towards Sustainability, a non-profit organization that drives change toward sustainability (Melles et al , 2022). China has the Instruction on Social Responsibility Report of Shanghai’s Civilized Organizations (Yalin et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there are many benefits resulting from the adoption of sustainability reporting, such as the internationalization of the institution (Calitz et al , 2018; Hassan et al , 2019; Kräusche and Pilz, 2018; Sassen et al , 2018; Zorio-Grima et al , 2018), attraction for the best stakeholders to be a part of the university (engaged employees and students) and improve interest for external investors (Hassan et al , 2019; Kräusche and Pilz, 2018; Trireksani et al , 2021; Zheng et al , 2020), better communication related to corporate social responsibility (Calitz et al , 2018; Hassan et al , 2019; Klußmann et al , 2019; Kräusche and Pilz, 2018; Larrán Jorge et al , 2019; Melles et al , 2022; Moggi, 2019; Nicolò et al , 2021; Sepasi et al , 2018; Yáñez et al , 2019; Zheng et al , 2020), contribution for the sustainable development issues, acquirement of better processes and greater visibility for the community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed University Food Environment Assessment tool was assessed as reliable, and a pilot test identified moderate diversity in food environments in Australia. Melles et al [87] aimed to provide a country-specific but sector-wide study of campus sustainability in the case of Australia as portrayed in reports, plans and targets and found that higher education institutes present weak institutionalization of sustainability and sector benchmarking could be beneficial.…”
Section: Sustainability Benchmarking In Higher Educationmentioning
confidence: 99%
“…A sustainable lifestyle is associated with green and environment-friendly society (Qazi et al ., 2021; Gigauri and Djakeli, 2021; Khan et al ., 2021). Studies show that sustainability in the higher education sector still lacks institutionalization and formalization of planning and reporting, although trends towards the usage of renewable energy and decrease of emissions are visible (Melles et al ., 2022). The experience of commercial companies regarding the reporting of social and environmental performances could also be a source of inspiration for universities considering the complexity of the phenomenon but also the need to publish data as detailed and structured as possible to ensure proper information of stakeholders.…”
Section: Literature Reviewmentioning
confidence: 99%